EMPOWERMENT OF LIPAS GROUPS FOR OPTIMIZING CLIENT INDEPENDENCE GUIDANCE AT GRIYA ABHIPRAYA CLASS I CORRECTIONAL CENTER SURABAYA - Prameswara, Bintang Wisnu (Universitas Nusa Cendana, 2025)
The goal of Community Guidance is to support correctional clients in addressing their challenges during the transition after release and to facilitate their reintegration into society. This guidance aims to help clients adapt, develop positive behaviors, and become productive citizens. One key program offered by Bapas is the Independence Guidance Program, which focuses on equipping clients with new skills or enhancing existing ones to prepare them for reintegration. However, challenges such as limited instructor availability and budget constraints affect the implementation of this guidance. The introduction of the Community-Based Corrections Group (Pokmas Lipas) through Director General of Corrections Decree No. PAS-06.OT.02.02 of 2020 provides an alternative solution to these limitations. This research employs a qualitative approach to analyze the dynamics of independence guidance, revealing significant improvements following the establishment of Pokmas Lipas. Supported by Griya Abhipraya, which serves as a platform for both Pokmas Lipas and correctional clients, this initiative optimizes independence guidance by offering a permanent space, expert personnel, structured programs, and operational funding independent of budget constraints. In conclusion, the presence of Pokmas Lipas at Griya Abhipraya enhances the quality of independence guidance and significantly aids clients in overcoming their challenges. Keywords: Empowerment; Independence Guidance; Pokmas Lipas